Distinguished Alumni: Roger F. Honberger, School of Architecture and Environmental Design (1975)
Roger F. Honberger rides by Betty's in a classic Ford V8 B 400 in the 1975 Homecoming Parade. Honberger was part of the School of Architecture and Environmental Design. Bank of America can be seen in the far left background.